Deep pyriform space augmentation with high G′ hyaluronic acid for nasolabial fold correction: a retrospective clinical study - Rauso, Raffaele; Zerbinati , Nicola (Aesthetic Medicine, 2026)
Introduction: The nasolabial fold is a primary aesthetic concern associated with facial aging. Traditional superficial filler techniques may correct wrinkles, however they often cause unnatural fullness of the perioral region. Deep structural support of the pyriform space may provide a more natural and anatomically congruent correction.Objectives: To evaluate the safety and aesthetic efficacy of deep periosteal injections of high G′ hyaluronic acid in the pyriform space for correction of the nasolabial folds. The primary endpoint of the study was patient-reported aesthetic improvement, assessed through a Visual Analog Scale (VAS) at 6 months after treatment. Secondary endpoints included procedural safety, incidence of adverse events, and patient-reported pain during the procedure. In addition, the influence of the presence of a local anesthetic (mepivacaine) in the filler formulation on pain perception was analyzed.Materials and Methods: A retrospective analysis of 52 patients (21 males, 31 females; mean age 44.5 years) treated between 2022 and 2025 was conducted. Treatments included deep pyriform space injection alone (n=14), combined with superficial intradermal nasolabial fold injections (n=8), or as a complementary procedure for midface enhancement (n=30). HA filler volumes ranged from 0.2–0.4 mL per side. Pain perception was recorded immediately post-procedure. Aesthetic outcomes were assessed using a Visual Analog Scale (VAS) at 6 months.Results: No vascular adverse events occurred. Transient edema and erythema were observed in all cases, resolving spontaneously within 24–48 hours. Patients reported filler palpability without visible contour irregularities. Mean pain scores were 8.2 for fillers without mepivacaine and 5.8 with mepivacaine. Mean aesthetic satisfaction VAS at 6 months was 8.6. In a subset followed up to 24 months, results remained stable.Conclusions: Deep pyriform space augmentation with high G′ HA is a safe and effective approach for the correction of nasolabial folds. By restoring skeletal support, this technique achieves natural, harmonious results while minimizing the risk of unnatural perioral fullness. The inclusion of a local anesthetic significantly reduces procedural pain.